Stepping‐stones across space and time: repeated radiation of Pacific flightless broad‐nosed weevils (Coleoptera: Curculionidae: Entiminae: Rhyncogonus). (2nd January 2017) - Claridge, Elin M.; Gillespie, Rosemary G.; Brewer, Michael S.; Roderick, George K.
Abstract: Aim: We examine spatial and temporal patterns of diversification among flightless weevils in the genus Rhyncogonus (Curculionidae: Entiminae), with respect to their passive mode of dispersal by rafting or upon birds and the geological context of Pacific island archipelagos. Location: Archipelagos and islands of the Pacific Ocean, especially the South Pacific and Hawaii. Methods: Nuclear and mitochondrial DNA sequence data were used in Bayesian and maximum likelihood analyses to generate a phylogenetic hypothesis for all available species within the genus Rhyncogonus, plus representatives of other tribes in the subfamily Entiminae. Bayesian inference with molecular and geological calibration points was also used to estimate the age of major lineages of Rhyncogonus and infer the history of colonization. Results: The genus Rhyncogonus has colonized all major archipelagos in the central Pacific, with multiple species occurring within nearly all archipelagos. The common ancestors of the genus were present in the central Pacific at least 15 Ma, probably first inhabiting islands now under water. Subsequent colonization and diversification across Oceania shows a pattern that is remarkably consistent with the geology of the region: the weevils, which likely disperse either by rafting on vegetation or on migratory birds, reached each island not long after its appearance. Main conclusions: Though flightless, weevils in the genus Rhyncogonus have been remarkably effective at colonizing islands of the Pacific and appear to have colonized more remote islands via a series of less remote archipelagos. Although such a process of dispersal has been predicted, this study provides the first clear demonstration of the role of stepping‐stones in the diversification of a lineage with passive dispersal.